Legal Certainty of Criminal Liability for Money Laundering in Corruption Cases Commited by Members of the Indonesian National - Kasim, Kasim; Sahlepi , Muhammad Arif; Ismaidar, Ismaidar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to investigate the effectiveness of the Cooperative Learning approach in improving students' critical thinking and learning outcomes. Critical thinking is a core skill required for effective learning, yet many students struggle to develop this ability. The Cooperative Learning approach has been recognised as effective in improving engagement, collaboration and understanding of concepts in learning. However, research specifically exploring the impact of the Cooperative Learning approach on critical thinking and learning outcomes is limited. This research used a qualitative desk study approach to investigate the role of Cooperative Learning in improving critical thinking and learning outcomes. An in-depth literature review was conducted to gather evidence from various previous studies relevant to this topic. The results showed that the Cooperative Learning approach has a positive impact in improving students' critical thinking.